Microsoft SQL server 2000 : performance optimization and tuning handbook - England, Ken, 1955- (Digital Press, 2001)
Learn from a SQL Server performance authority how to make your database run at lightning speed. Ken England's SQL Server 6.5 Performance Optimization and Tuning Handbook is recognized by SQL Server administrators as the indispensable guide to tuning and optimization. Now he's revised the book for Microsoft's new SQL Server 2000, the most advanced and powerful version yet of SQL Server, which takes full advantage of Windows 2000's new processing capabilities. The book details the factors that determine database performance and offers readers tools, techniques and best practices they can use to.